Pengaruh Daya Ledak Otot Tungkai dan Kelentukan Pinggang sebagai Prediktor Tendangan Melingkar Atlet Pencak Silat - Alfiqroam Kumar; Ali Mardius; Ary Suud Cahyo Alben (Jurnal Muara Olahraga, 2024)
This study aims to measure the ability of circular kicks through tests on the explosive power of the leg muscles and waist flexibility of pencak silat athletes in the city of Padang. Data was collected using the Standing Broad Jump to measure leg muscle explosive power, the Sit and Reach test to measure waist flexibility, the Grid Concentration Test to measure concentration, and the circular kick test to measure Circular Kicks. The results of data analysis show that: (1) Explosive Power of the Leg Muscles has a direct and significant effect on Circular Kicks by 12.96%. This means that the stronger a pencak silat athlete, the better the circular kick will be optimally. (2) Waist Flexibility has a direct and significant effect on Circular Kicks by 12.67%. (3) Concentration has a direct and significant effect on Circular Kicks by 2.04%. (4) The explosive power of the leg muscles has an indirect effect on the Circular Kick through Concentration of 14.94%. (5) Waist Flexibility has an indirect effect on Circular Kicks through Concentration of 15.44%. (6) Leg muscle explosive power, waist flexibility and concentration simultaneously influence the Circular Kick by 27.67%. Keywords: Leg muscle explosive power, Determination, and Circular Kick